Opportunities for the application of Red-edge reflectance-based indices in coastal vegetation and agro-ecological studies - Mukaromah, Laily; As-syakur, Abd. Rahman; Prastowo, Erwin (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019), 2019)
Remote sensing is an advanced tool that provides electromagnetic information about the Earth's surface and atmosphere. In ecological studies, the applications of vegetation indices (VIs) derived from remote sensing data have continued to increase, especially in capturing and monitoring vegetation properties and environmental changes. This study reviews the application of VIs with special focus on red-edge based indices in the evaluating coastal landscapes and other conservation studies. The spectral characteristics of vegetation is briefly reviewed in order to exploit the potential information of the reflectance spectrum, and the possible key role of vegetation indices in future research of coastal vegetation as well as resilience indicator in the ever-changing landscapes.